Soft functions for generic jet algorithms and observables at hadron colliders - Bertolini, Daniele; Kolodrubetz, Daniel; Neill, Duff; Pietrulewicz, Piotr; Stewart, Iain W.; Tackmann, Frank J.; Waalewijn, Wouter J. (The journal of high energy physics, 2017)
A bstract We introduce a method to compute one-loop soft functions for exclusive N - jet processes at hadron colliders, allowing for different definitions of the algorithm that determines the jet regions and of the measurements in those regions. In particular, we generalize the N -jettiness hemisphere decomposition of ref. [1] in a manner that separates the dependence on the jet boundary from the observables measured inside the jet and beam regions. Results are given for several factorizable jet definitions, including anti- k T , XCone, and other geometric partitionings. We calculate explicitly the soft functions for angularity measurements, including jet mass and jet broadening, in pp → L + 1 jet and explore the differences for various jet vetoes and algorithms. This includes a consistent treatment of rapidity divergences when applicable. We also compute analytic results for these soft functions in an expansion for a small jet radius R . We find that the small- R results, including corrections up to O R 2 , accurately capture the full behavior over a large range of R .